2020
DOI: 10.1073/pnas.1920469117
|View full text |Cite
|
Sign up to set email alerts
|

Prototypical pacemaker neurons interact with the resident microbiota

Abstract: Pacemaker neurons exert control over neuronal circuit function by their intrinsic ability to generate rhythmic bursts of action potential. Recent work has identified rhythmic gut contractions in human, mice, and hydra to be dependent on both neurons and the resident microbiota. However, little is known about the evolutionary origin of these neurons and their interaction with microbes. In this study, we identified and functionally characterized prototypical ANO/SCN/TRPM ion channel-expressing pacemaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 78 publications
8
49
0
Order By: Relevance
“…Likewise, the dramatic increase in the expression of the marker of cholinergic neurons ( chat ) in the initial 24 hpi, suggests that this neuronal type may be important in the innate immune response to C. albicans infection. This is consistent with the idea that certain neuronal groups can act as immunocompetent cells, which is an ancient function conserved between pre-bilaterians and mammals ( Godinho-Silva et al, 2019 ; Klimovich et al, 2020 ). Indeed, murine nociceptive neurons are critical for the innate immune response to cutaneous infection with C. albicans ( Kashem et al, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, the dramatic increase in the expression of the marker of cholinergic neurons ( chat ) in the initial 24 hpi, suggests that this neuronal type may be important in the innate immune response to C. albicans infection. This is consistent with the idea that certain neuronal groups can act as immunocompetent cells, which is an ancient function conserved between pre-bilaterians and mammals ( Godinho-Silva et al, 2019 ; Klimovich et al, 2020 ). Indeed, murine nociceptive neurons are critical for the innate immune response to cutaneous infection with C. albicans ( Kashem et al, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…An earlier study by the same group, indicated that neurons themselves play direct immune roles by producing antimicrobial factors, such as antimicrobial peptides ( 18 ), that can alter the composition of the microbial communities on the body ( 19 ). Here, Klimovich et al ( 2 ) extend their earlier findings and demonstrate that all neurons in the Hydra body, including the N2 pacemaker cluster, produce a rich repertoire of antimicrobial peptides and proteins, as well as many components of pathogen recognition receptors, such as Toll-like receptors, NOD-like receptors, C-type lectin, etc., indicating that they are immunocompetent cells with critical roles in immune signaling. Stressing further the role of Hydra neurons to immunity, the authors used bioinformatics and machine learning algorithms to demonstrate that a large fraction of neuronal genes unique to this genus, are capable of encoding antimicrobial peptides.…”
Section: Immunological Functions Of Neuronssupporting
confidence: 53%
“…By analyzing larvae carrying a mutation at the ret locus, the activity of which is required for the development of enteric neurons, Wiles et al ( 20 ) demonstrated that changes in peristalsis alter the relative abundance and distribution of specific bacterial species along the intestine of zebrafish. Based on the findings of Klimovich et al ( 2 ), it is possible that some of the effects observed in the zebrafish study could be due to direct and selective antimicrobial activities of enteric neurons. Characterization of the transcriptomes of enteric neurons in zebrafish, mouse, and human gut will generate valuable resources for establishing the range of antimicrobial factors produced by the intestinal neural networks of vertebrates.…”
Section: Immunological Functions Of Neuronsmentioning
confidence: 95%
See 2 more Smart Citations